2020
DOI: 10.33393/jcb.2020.2164
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound and biomarkers in primary care: Partners for a better management of patients with heart failure?

Abstract: Introduction: The association of pulmonary congestion assessed by lung ultrasound (LUS) and biomarkers—other than N-terminal pro-brain natriuretic peptide (NT-proBNP)—is uncertain. Methods: We investigated the relationship between total B-line count by LUS and several biomarkers in outpatients with suspicion of heart failure (HF). Primary care patients with suspected new-onset nonacute HF were evaluated both with a 12-scan LUS protocol (8 anterolateral areas plus 4 lower posterior thoracic areas) and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In relation to the prognostic value of NT-proBNP in this study, through ROC curve analysis, the probability of predicting admission and cardiovascular death this was evaluatedm and we observed that values above 3000 pg/mL were quite likely to predict the primary endpoint. These results are similar to previous reports [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In relation to the prognostic value of NT-proBNP in this study, through ROC curve analysis, the probability of predicting admission and cardiovascular death this was evaluatedm and we observed that values above 3000 pg/mL were quite likely to predict the primary endpoint. These results are similar to previous reports [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although LUS and CA125 are both congestion and short‐term prognostic markers, 34,35 there is little evidence of their association in acute and chronic HF. Our finding supports hypothesized correlations between B‐lines and cardiac biomarkers other than CA125 in HF patients, as we have previous reported 36 …”
Section: Discussionsupporting
confidence: 93%
“…Our finding supports hypothesized correlations between B‐lines and cardiac biomarkers other than CA125 in HF patients, as we have previous reported. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The use of LUS at the stage of outpatient diagnostics is beneficial for not only the patient and physician, indeed given its cost‐effectiveness it should also be viewed in light of its potential for health care system costs reduction 173–175 . Numerous examples of the use of US in the diagnostics of adults and children in outpatient treatment and even during home visits have been described 176–183 . The use of US in the GP office reduces the time to make an accurate diagnosis, helps in making therapeutic decisions and may improve the patient's prognosis 184,185 .…”
Section: Methodsmentioning
confidence: 99%
“… 173 , 174 , 175 Numerous examples of the use of US in the diagnostics of adults and children in outpatient treatment and even during home visits have been described. 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 The use of US in the GP office reduces the time to make an accurate diagnosis, helps in making therapeutic decisions and may improve the patient's prognosis. 184 , 185 Moreover, LUS used as point‐of‐care examination method may reduce disproportions in the quality of medical services depending on the place of residence and reduce the costs of patient care.…”
Section: Methodsmentioning
confidence: 99%